2006
DOI: 10.1371/journal.pone.0000039
|View full text |Cite
|
Sign up to set email alerts
|

A Virtual Reprise of the Stanley Milgram Obedience Experiments

Abstract: BackgroundStanley Milgram's 1960s experimental findings that people would administer apparently lethal electric shocks to a stranger at the behest of an authority figure remain critical for understanding obedience. Yet, due to the ethical controversy that his experiments ignited, it is nowadays impossible to carry out direct experimental studies in this area. In the study reported in this paper, we have used a similar paradigm to the one used by Milgram within an immersive virtual environment. Our objective ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
306
0
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 500 publications
(345 citation statements)
references
References 26 publications
9
306
0
4
Order By: Relevance
“…Although not directly tested, users may have felt spontaneously guilty independent of their awareness that the depicted violence was not real. Such a notion is speculative, but corresponds to a growing amount of research indicating that users automatically respond to virtual environments to a certain extent as though they were real (Bailenson, Blascovich, Beall & Loomis, 2003;McCall et al, 2009;Nass & Moon, 2000;Slater et al, 2006;Weber, Ritterfeld, & Mathiak, 2006;Yee, Bailenson, & Ducheneaut, 2009). Bailenson et al (2003) argue that users respond to real and virtual settings in a similar way only in terms of their automatic responses, yet distinguish between real and virtual settings when utilizing consciously controlled processes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although not directly tested, users may have felt spontaneously guilty independent of their awareness that the depicted violence was not real. Such a notion is speculative, but corresponds to a growing amount of research indicating that users automatically respond to virtual environments to a certain extent as though they were real (Bailenson, Blascovich, Beall & Loomis, 2003;McCall et al, 2009;Nass & Moon, 2000;Slater et al, 2006;Weber, Ritterfeld, & Mathiak, 2006;Yee, Bailenson, & Ducheneaut, 2009). Bailenson et al (2003) argue that users respond to real and virtual settings in a similar way only in terms of their automatic responses, yet distinguish between real and virtual settings when utilizing consciously controlled processes.…”
Section: Discussionmentioning
confidence: 99%
“…Results showed that White participants shot armed African American soldiers more quickly than White soldiers, suggesting that the ethnicity of the virtual characters activated participants' stereotypes. A later study by Slater et al (2006) replicated the Milgram obedience experiment in a virtual setting. Participants followed orders to give lethal electric shocks to a virtual stranger.…”
Section: Different From Playing Chess: the Moral Significance Of Virtmentioning
confidence: 97%
“…For instance, to test participant's fear responses, VR was used to create a ‘room 101’ with disturbing events such as spiders crawling around, explosions, and a floor collapsing (McCall et al ., 2015). Studies from the Slater group include a recreation of the famous Milgram experiment where participants had to execute fatal electric shots to a virtual character (Slater et al ., 2006); a violent fight scenario (Slater et al ., 2013) and a moral dilemma with an active shooter (Pan & Slater, 2011). In the latter, participants thought their task was to operate a lift in a gallery in VR, but later were shocked to be confronted with a tough decision: A gunman entered the lift and started shooting, and within a few seconds they had to choose whether they should push a button to save five people but sacrificing one other, who would otherwise be fine.…”
Section: The Munros – Challenges In the Implementation Of Vrmentioning
confidence: 99%
“…In front of them they could see an audience composed of a small number of animated virtual characters. [14], the London underground [2], the Milgram recreation [16], the virtual bar [11], the socially anxious virtual character [12] and the medical consultation [13].…”
Section: Slater's Experiments On Virtual Charactersmentioning
confidence: 99%